DEM-Based Watershed Delineation and Hydrological Parameter Extraction for HEC-HMS Modeling in Karangnongko Dam, Bojonegoro - Nabila Dinda Safitri; Novie Handajani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study applied DEM-based automatic watershed delineation using QGIS to derive hydrological parameters and develop a basin model for the Karangnongko Watershed, Bojonegoro. The delineation process successfully produced watershed boundaries, stream networks, and subbasin configurations consistent with the study area's topographic characteristics. Hydrological parameters such as watershed area, stream length, basin slope, and flow path characteristics were extracted from DEM analysis and used as input to develop the HEC-HMS basin model. The final model consists of 3 subbasins, 1 reach, and 1 junction, arranged according to the drainage hierarchy obtained from the delineation results. The results show that the accuracy of watershed delineation and hydrological parameter extraction is strongly influenced by DEM quality, preprocessing steps, and stream threshold selection. Proper DEM preprocessing, particularly sink filling and flow direction correction, improves drainage continuity and produces more reliable watershed representation. In general, integrating GIS-based delineation with HEC-HMS provides an efficient approach to hydrological modeling. This method improves spatial consistency, reduces manual interpretation during basin development, and supports more reliable preparation of hydrological parameters for watershed analysis. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land